How to improve superlubricity performance of diketone at steel interface: Effects of oxygen gas - Yuanyuan Jiang; Lei Chen; Chen Xiao; Shumin Zhang; Chenhui Zhang; Ningning Zhou; Tao Qin; Linmao Qian; Jiyang Zhang (Friction)
Abstract Achievement of steady and reliable super-low friction at the steel/steel contact interface, one of the most tribological systems applied for mechanical moving parts, is of importance for prolonging machine lifetime and reducing energy consumption. Here we reported that the superlubricity performance of the steel/steel sliding interface lubricated with tiny amounts of diketone solution strongly depends on the oxygen content in surrounding environment. The increase of oxygen not only significantly shortens the initial running-in time but also further reduces the stable coefficient of friction in superlubricity stage due to the enhancement of tribochemical reactions. On the one hand, more severe oxidation wear occurring at higher oxygen content facilitates material removal of the contact interface, lowering the contact pressure and the corresponding initial friction. On the other hand, the growth of iron ions during the shear process in high oxygen environment promotes the formation of chelate which acted as an effective lubricated film chemisorbed at the steel/steel friction interface to further lower the interfacial friction. The results provide a new opportunity to further optimize the tribological performance of diketone superlubricity system, especially towards the lubrication of mechanical engineering materials.